Assessment of the Importance of Tympanic Membrane Mechanoreceptors on Eustachian Tube Function Based on Pressure Chamber Measurements. Issue 3 (March 2018) - Meyer, Moritz F.; Schoch, Anja; Jansen, Stefanie; Hüttenbrink, Karl-Bernd; Beutner, Dirk
Abstract : Introduction: Previously, it was demonstrated how the Eustachian tube (ET) opening function can be influenced by middle ear pressure and movement of the tympanic membrane via neural control. Mechanoreceptors on the tympanic membrane may be part of the afferent arc and could influence the middle ear pressure by activating the musculus veli palatini as part of a reflex. Methods: In a hypo and hyperbaric pressure chamber, 17 participants (34 ears) were twice exposed to a standardized pressure profile of pressure decrease and increase. The ET function reflecting parameters—ET opening pressure (ETOP), ET opening duration (ETOD), and ET opening frequency (ETOF)—were determined before and after local anesthesia of the right tympanic membrane. Results: After pressure exposure by pressure increase (active induced equalization) and pressure decrease (passive equalization) there was no significant difference between the mean value of ETOP, ETOD, and ETOF before and after local anesthesia of the right tympanic membrane on the right (anesthetized) or left side (not anesthetized). Conclusion: These results may lead to the hypothesis that tympanic membrane mechanoreceptors may play a minor role in regulating the ET function in humans.